Etika Kesundaan dan Perilaku Ekonomi Pengusaha Kerupuk Muslim Asal Ciamis di Kabupaten Sleman, Yogyakarta=The Sundanese Ethic and The Economic Behaviour of Muslim Kerupuk Entrepreneurs from Ciamis in Sleman District of Y - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This research aims to describe in detail the economic behavior and the motivations that drive the muslim kerupuk entrepreneurs from Ciamis, West Java in Sleman District of Yogyakarta. Whether their economic behavior is based on subsistence demand that constitutes an exigency resulting from the effects of globalizing capitalism penetration